CIVIC EDUCATION ROLE FOR DEVOLVED STUDENT AWARENESS AS A GLOBAL CITIZEN - Prayoga Bestari, Redi Yamanto, Dasim Budimansyah, (Jurnal Civicus, 2015)
Civic education right now is not about prepare young generation to became good citizen. Civic education must also prepare young generation to become active as global citizen. This condition is effect of the world that interconnected in every area of life. So the young generation must be preparing for this challenge. This study is using qualitative approach with case studies method. The result of this study is showing that student at University Pasundan Bandung has knowledge to became global citizen. But their skill has not shown an attitude as a global citizen.